Pearson's marrow-pancreas syndrome. A multisystem mitochondrial disorder in infancy. - Rötig, A (1990)
Pearson's marrow-pancreas syndrome (McKusick No. 26056) is a fatal disorder of hitherto unknown etiology involving the hematopoietic system, exocrine pancreas, liver, and kidneys. The observation of high lactate/pyruvate molar ratios in plasma and abnormal oxidative phosphorylation in lymphocytes led us to postulate that Pearson's syndrome belongs to the group of mitochondrial cytopathies. Since rearrangements of the mitochondrial genome between direct DNA repeats were consistently found in all tissues tested, our results show that this disease is in fact a multisystem mitochondrial disorder, as suggested by the clinical course of the patients. Based on these observations, we would suggest giving consideration to the hypothesis of a defect of oxidative phosphorylation in elucidating the origin of other syndromes, especially those associated with an abnormal oxidoreduction status in plasma.